On construction of multidimensional circulant graphs of diameter two - E. A. Monakhova (Известия Томского политехнического университета: Инжиниринг георесурсов, 2009)
The paper considers the task of optimization of undirected circulant networks consisting in maximizing a number of nodes at predetermined graph degree and diameter. New lower bounds of a number of nodes for circulant networks of any degrees and diameter two were obtained. For the first time the infinite families of circulants of diameter two achieving the obtained bounds were constructed.